Excretory system of representatives from family Diplozoidae (Monogenea) - Konstanzová, V; Koubková, B; Kašný, M; Ilgová, J; Dzika, E; Gelnar, M (Parasitology research, 2016)
Diplozoons are representatives of blood-feeding ectoparasites from the family Diplozoidae (Polyopisthocotylea, Monogenea). Although these worms have been the subject of numerous taxonomical, phylogenetic, and ecological studies, the detailed study of their excretory system has remained relatively neglected. Our observations focused on the morphological and ultrastructural features of the excretory apparatus of four diplozoid species: Diplozoon paradoxum, Eudiplozoon nipponicum, Paradiplozoon bliccae, and Paradiplozoon homoion. Observations were obtained using two microscope methods: light microscopy, equipped with differential interference contrast (Nomarski DIC) and transmission electron microscopy (TEM). The ultrastructure of two basic compartments which forms the excretory apparatus, flame cells with filtration apparatus, and canal cells forming the protonephridial ducts is revealed in this study. A unique consecutive sequence of longitudinal semi-thin sections of the excretory pore of E. nipponicum is visualized there for the first time.
Keywords: Flame cell; druhová specificita; Diplozoidae; Excretory system; Animals; Protonephridia; Ultrastructure; Monogenea; zvířata; Species Specificity; Trematoda